Dinamika Interaksi Sosial di Era Dominasi Gawai: Perspektif Nilai Pancasila pada Mahasiswa Universitas Bhinneka PGRI - Ajar Dirgantoro; Andreas Andrie Djatmiko; Fidya Amalia (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The dominance of gadget use has changed the pattern of student social interactions, thus creating challenges in maintaining social values ​​in the university environment. This study aims to describe the dynamics of student social interactions in the era of gadget dominance and analyze the implementation of Pancasila values ​​in the social interactions of students in the Pancasila and Citizenship Education (PPKn) Study Program at Bhinneka PGRI University. The study used a qualitative approach with a phenomenological type. Informants were selected through purposive sampling technique. Data were collected through interviews, observation, and documentation, then analyzed using an interactive analysis model that includes data reduction, data presentation, and conclusion drawing, with validity testing through source and technique triangulation. The results show that student social interactions develop in a hybrid form of interaction that combines face-to-face and digital communication. The use of gadgets provides benefits in the form of ease of communication, access to information, and academic coordination, but also gives rise to phubbing behavior, reduced intensity of direct interaction, and the potential for miscommunication. Nevertheless, Pancasila values, such as empathy, tolerance, respect for diversity, and deliberation, remain implemented in student social life. These findings indicate that the dominance of gadgets does not eliminate the values ​​of Pancasila, but encourages the transformation of social interaction patterns that are more adaptive to the development of digital technology.